Gender and sexuality in the workplace - Williams, Christine L., 1959-; Dellinger, Kirsten (Bingley, U.K. : Emerald, 2010)
This volume features sociological research and theory on gender and sexuality in the workplace, and identifies how organizations can achieve a gender-balanced and sexually-diverse work force. While identifying characteristics of work organizations that have made important strides to achieving equality in the workplace, articles also detail how women and sexual minorities continue to face discrimination, harassment, and exclusion. Special attention is paid to how race and class shape the experience of discrimination for these groups. Topics discussed are wide-ranging and include: gender discrimination and the wage gap; sexual minorities (LGBT workers); homophobic and 'gay friendly' workplaces; sexual harassment; sex in the workplace; sex work and sex workers; gender equity policies; transgender workers; men and women in non-traditional jobs; occupational gender segregation; and, gender difference in work hours. "The Research in the Sociology of Work" series is proud to publish the works of new and established scholars on these important topics, including both quantitative and qualitative studies, as well as review essays that set the agenda for future sociological analysis.
Introduction / Christine L. Williams, Kirsten Dellinger -- Caring, curing, and the community : black masculinity in a feminized profession / Adia Harvey Wingfield -- Job satisfaction : impact of gender, race, worker qualifications, and work context / Dina Banerjee, Carolyn C. Perrucci -- "Not one of the guys" : women chefs redefining gender in the culinary industry / Deborah A. Harris, Patti A. Giuffre -- Women in power and gender wage inequality : the case of small businesses / Andrew M. Penner, Harold J. Toro-Tulla -- Navigating the boundaries : army women in training / Stacie R. Furia -- Gendered appearance norms : an analysis of employment discrimination lawsuits, 1970-2008 / Mary Nell Trautner, Samantha Kwan -- Gender variance in the Fortune 500 : the inclusion of gender identity and expression in nondiscrimination corporate policy / Christin L. Munsch, C. Elizabeth Hirsh -- Talk, touch, and intolerance : sexual harassment in an overtly sexualized work culture / Karla A. Erickson -- Sexual harassment and gendered organizational culture in Japanese firms / Kumiko Nemoto -- Fierce bitches on Tranny Lane : gender, sexuality, culture, and the closet in theme park parades / David Orzechowicz -- Making India the 'mother destination' : outsourcing labor to Indian surrogates / Sharmila Rudrappa.
Print version record
Keywords: Social Science -- Gender Studies; Business & Economics -- General; Medical / Pharmacology; Sociology: work & labour; Gender studies, gender groups; Sex role in the work environment; Gender identity in the workplace